Zig‐Zag Acridine/Sulfone Derivative with Aggregation‐Induced Emission and Enhanced Thermally Activated Delayed Fluorescence in Amorphous Phase for Highly Efficient Nondoped Blue Organic Light‐Emitting Diodes. Issue 6 (29th January 2018) - Li, Jie; Zhang, Rong; Wang, Ziqi; Zhao, Bo; Xie, Jingjuan; Zhang, Fang; Wang, Hua; Guo, Kunpeng
Abstract: Luminescent materials simultaneously exhibiting aggregation‐induced emission (AIE), superior luminous efficiency, and thermally activated delayed fluorescence (TADF) properties in amorphous phase are eagerly required for highly efficient nondoped organic light‐emitting diodes. In this contribution, an acridine/sulfone derivative, bis(3‐(9, 9‐dimethyl‐9, 10‐dihydroacridine)phenyl)sulfone (mSOAD), designed and synthesized by combing a diphenylsulfone (DPS) core with bi‐9, 9‐dimethyl‐9, 10‐dihydroacridine (DMAC) substituted at the 3, 3′‐positions is demonstrated. The highly twisted zig‐zag configuration endows the compound with desired frontier orbital distribution for extremely small energy gap between singlet and triplet states (Δ E ST = 0.02 eV) of TADF molecule and prominent AIE characteristic. More importantly, its amorphous sample displays enhanced quantum fluorescence yield as well as superior TADF characteristic, which exhibits advantage for device fabrication under thermal evaporation. Taking its suitable highest occupied molecular orbital/lowest unoccupied molecular orbital energy levels together, a nondoped blue electroluminescence device (CIE (0.18, 0.32)) based on mSOAD as the emitter yields an excellent maximum current efficiency, power efficiency, and external quantum efficiency of 31.7 cd A −1, 28.4 lm W −1, and 14.0%, which are 1.38‐, 1.25‐, and 1.25‐fold higher than those of its linear isomer DMAC–DPS (Δ E ST = 0.18 eV, with bi‐DMAC linked to DPS via 4, 4′‐positions)‐based device, respectively. Abstract : An aggregation‐induced emission active zig‐zag acridine/sulfone derivative with extremely small singlet–triplet energy gap (Δ E ST = 0.02 eV), simultaneously exhibiting enhanced luminescence efficiency and superior thermally activated delayed fluorescence in amorphous phase, affords a highly efficient nondoped blue organic light‐emitting diode with maximum electroluminescent efficiency of 31.7 cd A −1, 28.4 lm W −1, and 14.0%.